Beneficial Effects of Lactobacillus plantarum Strains on Non-Alcoholic Fatty Liver Disease in High Fat/High Fructose Diet-Fed Rats - Park, Eun-Jung (Nutrients, 2020)
Emerging evidence suggests that probiotics are beneficial in non-alcoholic fatty liver disease (NAFLD). This study aimed to explore the effects of two Lactobacillus plantarum strains, ATG-K2 and ATG-K6 (isolated from Korean fermented cabbage), in a rat model of high fat/high fructose (HF/HF) diet-induced NAFLD. Rats with NAFLD were randomized into four groups (HF/HF diet control, (HC); HF/HF diet with silymarin, (PC); HF/HF diet with ATG-K2, (K2); and HF/HF diet with ATG-K6, (K6)) with healthy rats on a normal diet serving as the negative control. After treatment, histopathological and biochemical analyses of the blood and liver tissue were conducted. In addition, fecal microbiota was analyzed using the MiSeq platform. Compared with HC rats, K2 and K6 rats experienced significantly lower body weight gain, displayed decreased hepatic lipid accumulation, had lower serum levels of aspartate aminotransferase and alanine aminotransferase, and showed increased antioxidant enzyme activities. Moreover, de novo lipogenesis-related genes were downregulated following K2 and K6 administration. The fecal microbiota of K2 and K6 rats contained a higher proportion of Bacteriodetes and a lower proportion of Fimicutes than that of HC rats. Taken together, our results suggest that L. plantarum strains ATG-K2 and ATG-K6 are potential therapeutic agents for NAFLD.